Implementasi Kebijakan Pencegahan Dan Penanggulangan Stunting Di Negeri Trana Kecamatan Teon Nila Serua Kabupaten Maluku Tengah - Yoan Litha Pormes; M. A. Rahawarin; Hengky V. R. Pattimuka (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research is a descriptive qualitative study that aims to analyze the Implementation of Stunting Prevention and Control Policies in Trana Village, Teon Nila serua sub-district, Central Maluku Regency. This research was conducted in Trana Village, Teon Nila Serua sub-district, Central Maluku Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved in the Stunting Prevention and Countermeasure Policy Implementation process in Trana Village, Teon Nila Serua sub-district, Central Maluku Regency. The results of the study are based on an analysis using the Van Meter and Van Horn policy implementation model which shows that there are still indicators that have not been achieved properly. Human resources at the lower level, especially cadres, are still lacking both in terms of quantity and quality. The characteristics of the implementing organization have not been fulfilled properly. The attitude of the implementers, especially in the community's understanding of the policy is still lacking. Communication and coordination are not optimal, because there are still activities that are not on target in their implementation. The conditions of the social environment, economic environment and political environment have not fully supported the success of stunting prevention and control policies.